The tattooist of Auschwitz [large type] : a novel - Morris, Heather (Screenwriter) (HarperLuxe, an imprint of HarperCollins Publishers, 2018)
"In April 1942, Lale Sokolov, a Slovakian Jew, is forcibly transported to the concentration camps at Auschwitz-Birkenau. When his captors discover that he speaks several languages, he is put to work as a Tatowierer (the German word for tattooist), tasked with permanently marking his fellow prisoners. Imprisoned for more than two and a half years, Lale witnesses horrific atrocities and barbarism--but also incredible acts of bravery and compassion. Risking his own life, he uses his privileged position to exchange jewels and money from murdered Jews for food to keep his fellow prisoners alive. One day in July 1942, Lale, prisoner 32407, comforts a trembling young woman waiting in line to have the number 34902 tattooed onto her arm. Her name is Gita, and in that first encounter, Lale vows to somehow survive the camp and marry her"--Publisher.